(untitled) (JONAH : Journal of Nursing and Homecare, 2022)
Advances in technology and globalization encourage people to experience changes in lifestyle. A lifestyle that was originally healthy, turned into an unhealthy lifestyle such as eating instant food, smoking, lack of exercise, drinking soft drinks or alcohol and overwork are risk factors for stroke. Stroke is a condition in which blood circulation in the brain is disrupted, causing tissue in the brain to die. Stroke can cause weakness or paralysis in one limb. This study was to increase muscle strength in body parts that experience weakness due to stroke which can interfere with one’s activities. This research is a descriptive case study with 2 research subjects and was conducted in April 2022. This study used interview, observation and physical examination techniques in collecting data with previously prepared instruments. The data is presented in the form of narration and tables. The results showed that there was an increase in the 2 subjects, where in the first subject there was an increase in the muscle strength scale from a scale of 3 to a scale of 4 and for the second subject there was also an increase in muscle strength from a scale of 3 to a scale of 4. There is a change in the increase in muscle strength in the provision of Range Of Motion (ROM) exercise in patients with impaired physical mobility due to stroke